Less frustration, more Activity—theoretical insights into frustrated lewis pairs for hydrogenation catalysis - Mane, M.V. (ChemCatChem, 2017)
The field of frustrated Lewis pair (FLP) chemistry has seen rapid development in only a few years. FLPs have performed most spectacularly in hydrogenation catalysis: a wide variety of FLP-based systems can catalyze the hydrogenation of a range of different substrates, including imines, enamines, ketones, alkynes, and alkenes. However, FLP-based hydrogenation catalysts are yet to match the efficiency of their transition-metal counterparts. The current investigation reveals an important aspect of FLPs that can be exploited to improve their efficiency, that is, the more sterically hindered the FLP catalyst is, the lower is its turnover frequency. Full quantum chemical calculations with DFT for a family of different, experimentally known hydrogenation FLP catalysts shows that superior FLP catalysts can be designed by reducing the frustration (by reducing the steric demand and acid/base strength) in the FLP. However, as lowering the steric demand without reduction in the frustration can result in unwanted side reactions, the design of the most efficient FLP catalysts depends on tuning the system so that both the steric demand and the frustration are reduced appropriately.
Keywords: Boranes; Hydrogenation; reaction mechanism; Steric Hindrance